A new variety of dianthus anatolicus (caryophyllaceae) from Turkey as evidenced by morphology and AFLP data - Aydin, Zübeyde Uğurlu; Koch, Marcus; Dönmez, Ali A. (Annales botanici Fennici, 2020)
Dianthus anatolicus var. afyonensis Uğurlu, M. Koch & Dönmez var. nova is described from central Turkey (Çay, Afyonkarahisar). It is morphologically different from D. anatolicus by stem, leaf and calyx length, and the shape of epicalyx scales and petals. We also used amplified fragment length polymorphism (AFLP) data to identify and circumscribe the new variety. Habitat, ecology and the conservation
Gesehen am 20.05.2021